Stem cell gene therapy for Fanconi anemia: report from the 1st International Fanconi anemia gene therapy working group meeting - Tolar, Jakub; Adair, Jennifer E; Antoniou, Michael; Bartholomä, Cynthia C.; Becker, Pamela S; Blazar, Bruce R; Bueren, Juan; Carroll, Thomas; Cavazzana-Calvo, Marina; Clapp, D Wade; Dalgleish, Robert; Galy, Anne; et al. (Molecular therapy, 2011)
Survival rates after allogeneic hematopoietic cell transplantation (HCT) for Fanconi anemia (FA) have increased dramatically since 2000. However, the use of autologous stem cell gene therapy, whereby the patient's own blood stem cells are modified to express the wild-type gene product, could potentially avoid the early and late complications of allogeneic HCT. Over the last decades, gene therapy has experienced a high degree of optimism interrupted by periods of diminished expectation. Optimism stems from recent examples of successful gene correction in several congenital immunodeficiencies, whereas diminished expectations come from the realization that gene therapy will not be free of side effects. The goal of the 1st International Fanconi Anemia Gene Therapy Working Group Meeting was to determine the optimal strategy for moving stem cell gene therapy into clinical trials for individuals with FA. To this end, key investigators examined vector design, transduction method, criteria for large-scale clinical-grade vector manufacture, hematopoietic cell preparation, and eligibility criteria for FA patients most likely to benefit. The report summarizes the roadmap for the development of gene therapy for FA.
Gesehen am 10.11.2022
Erstmals am 14. Dezember 2016 online veröffentlicht